Social Reproductive Labour: Exploring Experiences of Women in the Taxi Industry - Mlambo, Yonela (Department of Sociology, 2024)
The taxi- industry in South Africa is one of the most significant public modes of transport that employs a variety of workers, unskilled, under-skilled, and semi-skilled, and transport the majority of workers every day. The growth of the taxi-industry in South Africa is informed by the history of colonialism which ensued in the forced removal of black peoples from city vicinities, to the peripheries of the city which subsequently created transportation needs to and from work. Nonetheless, post-colonialism, the nationalist elite government ensued transformation endeavours and attempts to formalise the taxi-industry. However, the history of the taxi -industry in South Africa and post-colonial nationalist elites' government endeavours to transform the taxi-industry women are providing social reproductive labour in the taxiindustry are silenced. Therefore, the aim of this study was to uncover the experiences of women who produce social reproductive labour in the taxi-industry, and the gendered power dynamics in the taxi-industry by using semi-structured interviews. Semi-structured interviews are a dialogue between the interviewer and the interviewee and they were conducted at the Cape Town Deck Station taxi-rank. Semi-structured interviews were guided by qualitative research method largely because it enables the researcher to critically study the nature of phenomena, the phenomena qualities in their varying manifestations, and the context in which they manifest themselves or from the perspectives from which they can be perceived in their natural environment. This research found that the work provided by omama is integral for the functioning of the taxi industry as it provides them with labour power although it subject omama to precarious working conditions.